2016
DOI: 10.1021/acs.jpcc.6b00492
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Crystal Truncation Rod Studies of Surface Oxidation and Reduction on Pt(111)

Abstract: We present X-ray crystal truncation rods measurements of Pt(111) surface under electrochemical conditions. Analyses of crystal truncation rods reveal that surface oxide formation buckles the top surface layer of platinum to two different heights at the potential (0.95 V vs RHE) below the so-called place-exchange potential. While the anti-Bragg intensity, sensitive to the top surface layer, drops in response to the anodic charge transfers, its responses to the cathodic charge transfers are significantly delayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 30 publications
8
55
1
Order By: Relevance
“…It was found that the surface oxide forms in three distinctive steps. First, oxispecies adsorb to the surface with little effect structurally and chemically on the platinum surface . Second, at a high anodic potential, platinum atoms place‐exchange with oxygen atoms to form a bi‐layer oxide surface .…”
Section: Electrode Interface Studies With Conventional Surface X‐ray mentioning
confidence: 98%
“…It was found that the surface oxide forms in three distinctive steps. First, oxispecies adsorb to the surface with little effect structurally and chemically on the platinum surface . Second, at a high anodic potential, platinum atoms place‐exchange with oxygen atoms to form a bi‐layer oxide surface .…”
Section: Electrode Interface Studies With Conventional Surface X‐ray mentioning
confidence: 98%
“…A survey of recent high‐resolution CTR results using model refinement, direct methods, and hybrid approaches shows that the estimated uncertainty in the relative atomic positions (along the surface normal) is generally less than 0.1 Å (10 pm), the uncertainty in the occupancies is on the order or ≈5–10%, and bond/tilt angles can be determined with a precision a few degrees. [ 1,31,93–100 ]…”
Section: Theory and Measurement Of Ctrsmentioning
confidence: 99%
“…[93] A survey of recent high-resolution CTR results using model refinement, direct methods, and hybrid approaches shows that the estimated uncertainty in the relative atomic positions (along the surface normal) is generally less than 0.1 Å (10 pm), the uncertainty in the occupancies is on the order or ≈5-10%, and bond/tilt angles can be determined with a precision a few degrees. [1,31,[93][94][95][96][97][98][99][100] It should be noted that, for a full reconstruction of the electron density from CTR data, it is challenging to apply current phase retrieval techniques for more than ≈10-15 unknown surface or film layers. Therefore, the application of direct methods has been restricted to surface and thin film structures, while larger structures such as periodic superlattices have been analyzed via model refinement.…”
Section: Resolution Uncertainty and Limitationsmentioning
confidence: 99%
“…This way, secondary electrons are released from the Si surface, which can interact with the adsorbed DNA. Liu et al [22] performed LEE impact studies on plasmid DNA by generating the LEEs from the substrate surface through UV irradiation. 240-400 nm (3.1-5.2 eV) VUV irradiations of the n-Si substrates resulted in a significant amount of SSBs in the plasmid DNA.…”
Section: Introductionmentioning
confidence: 99%
“…240-400 nm (3.1-5.2 eV) VUV irradiations of the n-Si substrates resulted in a significant amount of SSBs in the plasmid DNA. [22] 1.1. Methods…”
Section: Introductionmentioning
confidence: 99%